Evaluación de factores de riesgos laborales y plan de mejora de seguridad en el proyecto Costa Garden - Gortaire Pulupa, Richard (2024)
The study "Assessment of Occupational Risk Factors and Safety Improvement Plan in the Costa Garden Project" focuses on optimizing occupational safety in civil engineering through a mixed approach combining quantitative and qualitative analyses. This method allows for a comprehensive assessment of occupational risks and the development of an improvement plan based on the integration of advanced technologies and a strong safety culture. The research is descriptive and correlational, highlighting the importance of detailing the risks and examining their relationship with the incidence of accidents. The methodology includes surveys, on-site observations, and interviews with workers and experts, identifying physical, chemical, ergonomic, and psychosocial risks, and evaluating current safety measures. The results show a generally positive perception of safety but point out specific risk areas such as working at heights and handling heavy machinery, in addition to highlighting the need for improvements in the use of PPE and interior lighting. The conclusion emphasizes the need for a detailed risk assessment, active involvement of workers in safety, and the implementation of an improvement plan that uses advanced technology and fosters a participatory safety culture. This approach not only improves safety but also promotes a healthier and more productive work environment, establishing a model for future construction projects.